Detection of respiratory pathogens in clinical samples using metagenomic shotgun sequencing. Issue 7 (28th May 2019) - Qi, Chao; Hountras, Peter; Pickens, Chiagozie Ononye; Walter, James M.; Kruser, Jacqueline M.; Singer, Benjamin D.; Seed, Patrick; Green, Stefan J.; Wunderink, Richard G.
Abstract : Purpose. In this pilot study, we used shotgun metagenome sequencing (SMS) strategy on bronchoalveolar lavage (BAL) samples from hospitalized patients with suspected ventilate-associated pneumonia (VAP) in order to explore its potential for improving detection of ventilator-associated-pneumonia (VAP) etiology. Methodology. In total, 67BAL samples from patients with VAP were tested with SMS strategy for detection of respiratory pathogens. Results of SMS and routine respiratory culture were compared. Results. SMS detected all pathogens recovered by cultivation approaches. In addition, putative pathogens other than the organisms recovered by culture were detected by SMS in culture-positive samples. In 40 of 45 (89  %) culture-negative samples, a potential pathogen was detected by SMS. Conclusion. This proof-of-concept study demonstrates that SMS is able to detect bacterial, fungal and viral organisms in BAL, including culture-negative cases.